2012
DOI: 10.1002/jso.23302
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐12 is associated with overall survival in Chinese patients with gastric cancer

Abstract: The study results showed that increased expression of MMP-12 was associated with tumor progression in gastric cancer. It also provided the first evidence for MMP-12 expression in gastric cancer as an independent prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…So it would contribute to identify high-risk patients who should receive more aggressive therapy, thus improve the prognosis of patients who received curative surgery. This prognostic value of MMP-12 in melanoma detected by the present study was consistent with findings in hepatocellular carcinoma, endometrial adenocarcinoma, and gastric cancer [13,16,17]. The possible explanation for the significant association of MMP-12 with melanoma progression and prognosis could attribute to the degradation of ECM and basement membrane by active MMP-12, which facilitate tumor cell invasion and metastasis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…So it would contribute to identify high-risk patients who should receive more aggressive therapy, thus improve the prognosis of patients who received curative surgery. This prognostic value of MMP-12 in melanoma detected by the present study was consistent with findings in hepatocellular carcinoma, endometrial adenocarcinoma, and gastric cancer [13,16,17]. The possible explanation for the significant association of MMP-12 with melanoma progression and prognosis could attribute to the degradation of ECM and basement membrane by active MMP-12, which facilitate tumor cell invasion and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…Active MMP-12 has broad substrate specificity, recognizing extracellular matrix proteins such as type I gelactin, fibronectin, laminin, vitronectin, proteoglycans, and fibrin, and it can also produce angiostatin from plasminogen. Expression of MMP-12 in vivo has previously been described in hepatocellular carcinoma, colorectal cancer, gastric cancer, renal cell carcinomas, pancreatic cancer, and in esophageal carcinoma [13][14][15][16][17][18]. However, the role of MMP-12 on cancer, favorable or unfavorable for tumor invasion and metastasis, seems to be tissue-type specific.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[30,31] Interestingly, 25.5% of these genes were primarily involved in cell adhesion, cell migration, extracellular matrix disassembly, blood vessel development, and wound healing associated with gastric adenocarcinoma metastases, such as collagen families, [20,23,32,33] fibronectin 1, [20,23,34] and matrix metalloproteinases (MMPs) families. [20,23,3539] Some cell proliferation-related genes, such as MYC, [20,23,40] cyclin E1, [20,23,41] CDC28 protein kinase regulatory subunit 1, [20,42,43] CDC28 protein kinase regulatory subunit 2, [23,43] cyclin-dependent kinase 4, [20,23,44] and proliferating cell nuclear antigen, [20,44,45] EGFR, [20,44,46] FGFR4, [20,23] insulin like growth factor 2, [20] cell division cycle 25B, [47] human epidermal growth factor receptor 2, [44,45] and protein kinase, DNA-activated, catalytic polypeptide, [48] have been previously reported as showing extremely high levels of expression in gastric adenocarcinoma. A total of 37 genes, established in a large number of experimental and clinical studies, were selected for further study.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer patients, prognostic markers, including erb-b2 receptor tyrosine kinase 2 (ERBB2) (26,27), CD44 (28,29) and matrix metallopeptidase 12 (30) have been reported. Additionally, a previous study by the present team demonstrated that the expression of the microRNAs mir-20b and mir-150 may be a prognostic marker for undifferentiated gastric cancer (1).…”
Section: Discussionmentioning
confidence: 99%